Near or far away: local police governance in Ireland - Conway, Vicky (European journal of criminology, 2019)
This paper will outline the extent to which local police governance is provided for in Ireland. It will argue that, in a country that has of late been plagued by policing scandals, reform agenda as yet have not been preoccupied by this issue and so formal police governance has not emerged. On the other hand, however, the paper analyses reform trends that tend towards such developments. These are analysed and it is argued, firstly, that these developments have been substantially shaped by the post-colonial nature of the state and, secondly, that through these examples we can question the virtues and vices of local police governance.